Plastic material for plugging underground coal mine and preparation method thereof

By using three-component plastic materials composed of homemade gelling agent, potassium carbonate, sodium carbonate and white calcium-based bentonite, the existing underground sealing materials in terms of construction ease, cost-effectiveness, plasticity and long-term effectiveness are solved. The shortcomings have achieved efficient and economical blocking effect.

CN119391119APending Publication Date: 2025-02-07XUZHOU JI AN MINING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311276349.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing underground sealing materials for coal mines have shortcomings in construction simplicity, cost-effectiveness, plasticity and long-term effectiveness, which are difficult to meet the efficient sealing needs of the coal industry.

Method used

A plastic material consisting of three components: A, B and C. Material A is a homemade gelling agent, material B is an aqueous solution of potassium carbonate and sodium carbonate, and material C is white calcium-based bentonite. The material reacts without temperature rise at room temperature, has good diffusion and permeability, and can form paste-like gels in coal rocks, and has good adhesion and sealing properties.

Benefits of technology

It realizes a normal temperature reaction without thermal discharge, has good diffusion, permeability, adhesion and sealing properties, can twist and deform under the action of ore pressure, maintain a negative pressure state for a long time, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004477099990000061
    Figure BDA0004477099990000061
  • Figure HDA0004477100000000011
    Figure HDA0004477100000000011
  • Figure HDA0004477100000000012
    Figure HDA0004477100000000012
Patent Text Reader

Abstract

The invention discloses a plastic material for coal mine underground plugging and a preparation method thereof.The material is composed of a material A, a material B and a material C. The material A is prepared from, by mass, 30-50 parts of self-made gelling agent and 50-70 parts of water; the material B comprises the following components in parts by mass: 6-9 parts of potassium carbonate, 3-6 parts of sodium carbonate and 85-90 parts of water; the material C comprises the following components in parts by mass: 10-15 parts of white calcium bentonite; the material is free of temperature rise in reaction, rapid in reaction, good in diffusion and permeability, excellent in adhesion and plugging performance and good in plasticity, and can keep a negative pressure state for a long time after negative pressure pumping; during application, three components are pumped at the same time, operation is easy, performance is excellent, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a plastic plugging material, in particular to a plastic material used for plugging underground in coal mines and a preparation method thereof. Background Art

[0002] The plugging materials used in coal mines are mainly divided into two categories: inorganic cement mortar, high-water quick-setting materials, water glass-based materials, composite inorganic plugging materials and organic mining reactive polymer materials (polyurethane, phenolic, urea-formaldehyde, acrylate). Different plugging materials have different applicability under specific coal mine engineering conditions, and usually need to be selected according to the actual situation.

[0003] In the middle of the 20th century, Academician Zhou Shining of China University of Mining and Technology and others proposed a method of sealing with inorganic cement mortar, which involves mixing water and silicate cement in a certain water-cement ratio and then injecting the mixture into the space to be sealed using a mud pump.

[0004] The advantages of cement mortar plugging materials are that their plugging quality is not affected by water in the coal (rock) layer, they are easily available, low in cost, have high strength in the solidified body, and the cement mortar will not soften when it comes into contact with water after solidification. However, the cement mortar plugging process is cumbersome, takes a long time to solidify, has a low stone rate, and is prone to shrinkage and cracking in the later stage, causing plugging failure. At present, this plugging method has been basically eliminated in mines above a certain scale in my country.

[0005] High-water quick-setting materials have good fluidity, high injectability, and short slurry setting time. However, strict proportioning process and improper material proportioning will lead to the slurry not being able to solidify, the material not being expansive, and the material being prone to water loss and powdering under special circumstances.

[0006] Water glass-based materials have low cost, low viscosity and high injectability. However, they have low final strength, high disintegration, easy to shrink due to water loss, and cracking after solidification. In his doctoral dissertation "Research on Integrated Sealing Technology and Application of Gas Extraction and Plugging", Sun Zhidong of Henan Polytechnic University introduced in detail the types and advantages and disadvantages of plugging materials, and developed a low-cost, highly injectable, and controllable gel time particle-free "organic-inorganic" composite fracture plugging material, namely, isocyanate-modified water glass plugging material.

[0007] With the continuous development and improvement of new materials and new processes, plugging materials are no longer limited to single materials, and are gradually transitioning to composite plugging materials. These include: new CF materials, PD composite materials, etc. New CF materials have the advantages of high water-repellent materials and high compressive deformation resistance. They are mainly composed of inorganic additives such as ordinary silicate cement and gypsum. PD composite materials are similar to new CF materials, both of which are based on cement. The difference is that they use advanced microencapsulation technology, which can achieve slow penetration of slurry in the coal (rock) fracture system, gradually solidify and expand in the process, thereby achieving efficient plugging of the fractures.

[0008] Although the above modified composite plugging materials have expansion capabilities, they cannot fully adapt to a large degree of plastic deformation. Therefore, such materials have good application effects within a period of time after plugging, but it is difficult to maintain the plugging state for a long time.

[0009] Compared with inorganic material plugging, mining reactive polymer organic plugging materials and their supporting processes have the advantages of simple operation and less time consumption. They have been widely used in plugging operations in coal mines. Polyurethane materials have high foaming multiples, good adhesion and good plasticity, but their mechanical strength is low, viscosity is high, and the foaming speed is too fast and difficult to control. Phenolic materials have strong chemical stability, good water resistance and heat resistance, and flame retardancy, but their curing time is too long, they are easy to age after curing, the cost is too high, and phenol is highly toxic. Urea-formaldehyde materials are low in cost, small in specific gravity, low in thermal conductivity and high in safety factor, but they have low strength, poor flexibility, easy to age and crack, and some irritating gases will be released during the curing process. Acrylates have low viscosity, controllable solidification time, low permeability, certain expansion with water, non-toxic, but low in mechanical strength, certain irritating odor, and slightly higher price.

[0010] From the above analysis, it can be seen that seeking a new type of plugging material that is simple to construct, low cost, good plasticity, non-toxic and harmless, and can achieve long-term effective plugging has become a key scientific issue that needs to be urgently solved in the current coal industry. Summary of the invention

[0011] In order to solve the problem of large amount of heat release during the foaming and curing process of polymer materials, the present invention provides a plastic material for underground plugging in coal mines and a preparation method thereof. The material has no temperature rise, rapid reaction, good diffusion and permeability; and has excellent adhesion and plugging performance, good plasticity, and can maintain a negative pressure state for a long time after the negative pressure is pumped. When used, the three components are pumped simultaneously, the operation is simple, the performance is excellent, and it has broad application prospects.

[0012] To achieve the above object, the technical solution adopted by the present invention is:

[0013] A plastic material for underground plugging of coal mines, the material consisting of three components: material A, material B and material C, wherein the material A comprises 30-50 parts of a homemade gelling agent and 50-70 parts of water;

[0014] The composition of material B by weight is: 6-9 parts of potassium carbonate, 3-6 parts of sodium carbonate, and 85-90 parts of water;

[0015] The C material is composed of 10-15 parts by weight of white calcium-based bentonite.

[0016] Furthermore, the homemade gelling agent is made from the following raw materials in parts by weight:

[0017] 52-60 parts of butyl acrylate, 30-40 parts of isooctyl acrylate, 5-10 parts of styrene, 2-4 parts of acrylamide, 0.2-0.5 parts of diallyl phthalate, 5-8 parts of behenyl polyoxyethylene ether methyl methacrylate, 3-5 parts of octadecyl acrylate, 2-8 parts of sorbitan monooleate, 0.1-0.5 parts of stearyl alcohol polyoxyethylene ether, 2.5-4 parts of MES-30, 0.1-0.2 parts of Na2HPO4, 50-100 parts of initiator, and 230-260 parts of water.

[0018] Furthermore, the preparation method of the homemade gelling agent comprises the following steps:

[0019] S1: Weigh and add part of water, part of MES-30 and sorbitan monooleate according to the ratio into a pre-emulsification bottle, stir and mix, then weigh butyl acrylate, acrylamide, isooctyl acrylate, styrene, behenyl polyoxyethylene ether methyl methacrylate, octadecyl acrylate, diallyl phthalate according to the ratio and drop them into the pre-emulsification bottle in sequence, stir and mix, and prepare a stable pre-emulsion;

[0020] S2: taking out 5-10% of the pre-emulsion as the seed emulsion, and continuing to stir the remaining pre-emulsion as the core layer pre-emulsion for later use;

[0021] S3: Add the remaining water to the reaction system, dissolve Na2HPO4, stearyl alcohol polyoxyethylene ether, and sorbitan monooleate in water according to the ratio, stir and heat to 80-85°C, and stir at a speed of 120-160r / min;

[0022] S4: Add the seed emulsion and the first initiator in step S2 at 80-85°C, gradually drop the remaining core layer pre-emulsion and the second initiator, cool to 65-70°C after 2-4 hours and keep for 1-2 hours; then cool to 35-40°C, add the remaining emulsifier MES-30, stir evenly and discharge.

[0023] Furthermore, the initiator comprises a first initiator and a second initiator, the concentration of the first initiator is 5-10wt%, and the concentration of the second initiator is 2-5wt%.

[0024] Furthermore, the first initiator and the second initiator are both selected from any one of ammonium persulfate, potassium persulfate and azobisisobutyronitrile.

[0025] Furthermore, the mass fraction of water added in step S1 is 100-120 parts.

[0026] Furthermore, the mass fraction of MES-30 added in step S1 is 2-3 parts.

[0027] Furthermore, the mass fraction of the first initiator added in step S4 is 30-50 parts.

[0028] Another object of the present application is to provide a method for preparing a plastic material for underground plugging in coal mines, comprising the following steps:

[0029] S1: Add the homemade gelling agent into water according to the proportion, stir evenly to obtain material A;

[0030] S2: Add sodium carbonate and potassium carbonate into water according to the ratio, stir evenly to obtain material B;

[0031] S3: Add water to material C to form solution C, with a mixing mass ratio of 1:2.5-4;

[0032] S4: During the grouting process, material A, material B and solution C are mixed in a mass ratio of 2:2:1 and injected into the area to be plugged.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) Room-temperature reaction: The innovative material of this application does not generate heat during the reaction process and does not dissipate heat to the surrounding environment;

[0035] (2) Good diffusion and permeability: It has low initial viscosity, good diffusion and permeability, and can fully fill the voids and cracks around coal and rock;

[0036] (3) Excellent adhesion and plugging performance: The viscosity gradually increases with time, and it can effectively adhere to the coal and rock mass, and has good plugging performance for the fracture channel;

[0037] (4) Good plasticity: The material eventually forms a paste-like gel, which can be twisted and deformed under the action of mine pressure, instantly filling the new fracturing and crushing space;

[0038] (5) Flame retardant and good thermal stability: The paste-like gel does not burn or support combustion under high temperature fire sources of thousands of degrees. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 This is a graph showing the adhesion test results of a plastic material for plugging underground coal mines provided in Example 1 of the present invention;

[0041] Figure 2 A comparison diagram of the states before and after high-temperature flame baking of a plastic material for underground coal mine plugging provided in Example 1 of the present invention, wherein the high-temperature flame is directed toward the surface of the material to ignite, wherein (A) is during flame baking, and (B) is after the flame leaves; DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with specific embodiments.

[0043] The following examples all use homemade gelling agents synthesized by the following method:

[0044] 1. Raw materials include: deionized water, butyl acrylate, isooctyl acrylate, styrene, acrylamide, diallyl phthalate, behenyl polyoxyethylene ether methyl methacrylate, octadecyl acrylate, sorbitan monooleate, stearyl alcohol polyoxyethylene ether (O-20), sorbitan monooleate, disodium hydrogen phosphate (Na2HPO4), fatty alcohol polyoxyethylene ether sulfosuccinic acid monoester disodium salt (MES-30); initiator; all of the above are industrial products;

[0045] 2. Synthesis step: add 100 parts (all by mass) of deionized water, 2.5 parts of MES-30 and 3 parts of sorbitan monooleate into a pre-emulsification bottle, stir for 20 minutes, then add 60 parts of butyl acrylate, 3 parts of acrylamide, 35 parts of isooctyl acrylate, 8 parts of styrene, 6 parts of behenyl polyoxyethylene ether methyl methacrylate, 3 parts of octadecyl acrylate and 0.3 parts of diallyl phthalate dropwise into the pre-emulsification bottle in sequence, stir for 30 minutes to prepare a stable pre-emulsion;

[0046] Take out 6% of the pre-emulsion from the pre-emulsion bottle as the seed emulsion, and continue to stir the remaining pre-emulsion for 1 hour as the core layer pre-emulsion. In a four-necked flask equipped with a reflux condenser, a thermometer, and a stirrer, add 150 parts of deionized water, dissolve 0.1 parts of buffer Na2HPO4, 0.3 parts of stearyl alcohol polyoxyethylene ether (O-20), and 1.5 parts of dehydrated sorbitan monooleate in water, stir and heat to 85°C, and the stirring speed is 120-160r / min. Add 6% of the pre-emulsion and 30 parts of 5% ammonium persulfate aqueous solution at 85°C, gradually add the remaining core layer pre-emulsion and 40 parts of 2% azobisisobutyronitrile aqueous solution, and cool to 70°C after 3 hours and keep for 1 hour. Then cool to 40°C, add 0.5 parts of emulsifier MES-30, stir evenly and discharge.

[0047] Example 1

[0048] A plastic material for plugging underground in coal mines consists of three components: material A, material B and material C. The preparation method is as follows: 40 parts of a homemade gelling agent are added to 60 parts of water according to a ratio, and the material A is obtained after being stirred evenly; 3 parts of sodium carbonate and 7 parts of potassium carbonate are added to 90 parts of water according to a ratio, and the material B is obtained after being stirred evenly; 14 parts of white calcium-based bentonite, i.e., material C, are mixed with 36 parts of water to form a C solution; during the grouting process, material A, material B and solution C are mixed according to a mass ratio of 2:2:1, and the three materials are simultaneously pumped by a three-cylinder grouting pump and injected into an area to be plugged.

[0049] Example 2

[0050] A plastic material for plugging underground in coal mines consists of three components: material A, material B and material C. The preparation method is as follows: 45 parts of a homemade gelling agent are added to 55 parts of water according to a ratio, and the material A is obtained after being stirred evenly; 3 parts of sodium carbonate and 8 parts of potassium carbonate are added to 89 parts of water according to a ratio, and the material B is obtained after being stirred evenly; 12 parts of white calcium-based bentonite, i.e., material C, are mixed with 38 parts of water to form a C solution; during the grouting process, material A, material B and solution C are mixed according to a mass ratio of 2:2:1, and the three materials are simultaneously pumped by a three-cylinder grouting pump and injected into an area to be plugged.

[0051] Example 3

[0052] A plastic material for plugging underground in coal mines consists of three components: material A, material B and material C. The preparation method is as follows: 50 parts of a homemade gelling agent are added to 50 parts of water according to a ratio, and the material A is obtained after being stirred evenly; 4 parts of sodium carbonate and 9 parts of potassium carbonate are added to 87 parts of water according to a ratio, and the material B is obtained after being stirred evenly; 10 parts of white calcium-based bentonite, i.e., material C, are added to 40 parts of water to form a C solution; during the grouting process, material A, material B and solution C are mixed according to a mass ratio of 2:2:1, and the three materials are simultaneously pumped by a three-cylinder grouting pump and injected into an area to be plugged.

[0053] More preferably, the three-cylinder grouting pump used in the above embodiment is the 3ZBQS12-6 pump independently developed by Xuzhou Ji'an Mining Technology Co., Ltd.

[0054] Comparative Example 1

[0055] A material for plugging underground in coal mines consists of three components: material A, material B and material C. The preparation method is as follows: 40 parts of a homemade gelling agent are added to 60 parts of water according to a ratio, and the material A is obtained after being stirred evenly; 3 parts of sodium bicarbonate and 7 parts of sodium acetate are added to 90 parts of water according to a ratio, and the material B is obtained after being stirred evenly; 14 parts of white calcium-based bentonite, i.e., material C, are added to 36 parts of water to form a C solution; during the grouting process, material A, material B and solution C are mixed according to a mass ratio of 2:2:1, and the three materials are simultaneously pumped by a three-cylinder grouting pump and injected into an area to be plugged.

[0056] Comparative Example 2

[0057] A material for plugging underground in coal mines consists of three components: material A, material B and material C. The preparation method is as follows: 40 parts of a homemade gelling agent are added to 60 parts of water according to a ratio, and the material A is obtained after being stirred evenly; 10 parts of sodium sulfite are added to 90 parts of water according to a ratio, and the material B is obtained after being stirred evenly; 14 parts of white calcium-based bentonite, i.e., material C, are mixed with 36 parts of water to form a C solution; during the grouting process, material A, material B and solution C are mixed in a mass ratio of 2:2:1, and the three materials are simultaneously pumped by a three-cylinder grouting pump and injected into an area to be plugged.

[0058] The parameters that need to be tested for the plastic plugging material prepared by mixing material A, material B and material C in the embodiment include: reaction temperature rise, adhesion, non-flow time after reaction, and negative pressure value after vacuuming for 1 day after sealing with this material. The data tested in different embodiments are shown in Table 1:

[0059] Table 1 Performance test results of the three components of plastic plugging material after reaction

[0060]

[0061] Reaction temperature rise test: Before the reaction, place material A, material B and material C in a 25°C water bath for 1 hour. After the temperature stabilizes, take out the three components and mix material A, material B and material C in a mass ratio of 2:2:1. After mixing, insert an electronic digital thermometer into the center of the finished product, observe the changes in the thermometer reading, and calculate the reaction temperature rise. The test shows that the polymer of this application is polymerized at room temperature.

[0062] Adhesion test: Take a fixed mass of the finished product after the reaction, apply it on a 15cm*15cm glass plate, place the glass plate vertically, and observe the sliding state of the finished product on the glass plate. Figure 1This is a graph showing the adhesion test results of a plastic material for underground coal mine plugging provided in Example 1. It can be seen that the material is a paste-like gel and does not slide down.

[0063] Determination of non-flow time after reaction: Before the reaction, place material A, material B and material C in a 25°C water bath for 1 hour. After the temperature stabilizes, take out the three materials and mix material A, material B and material C in a mass ratio of 2:2:1. Start timing immediately after mixing and stop stirring after about 5 seconds. Stop timing when the beaker is tilted at 90° and the finished product does not slide at all. The time at this time is the non-flow time after reaction. The gelling time of the material in this application is within 10 seconds, and it will no longer flow within 25 seconds.

[0064] Negative pressure value change measurement: inject plastic plugging material into the piled gravel to fill the gravel cracks, extract air from the bottom of the container, monitor the negative pressure data change to monitor the plugging performance of the material. The initial air pressure is -0.060MPa. As time goes by, after 1 day, the air pressure value tends to stabilize and basically no longer decreases.

[0065] Flame retardancy test: High temperature flame is directed toward the surface of the material to ignite. Figure 2 The following is a comparison diagram of the states before and after high-temperature flame baking of a plastic material for underground coal mine plugging provided in Example 1, wherein (A) is during flame baking, and (B) is after the flame leaves. It can be seen that the paste-like gel does not burn or support combustion under a high-temperature fire source of thousands of degrees, showing excellent flame retardancy and thermal stability.

[0066] The principle of the present invention is that the synthesized gelling agent contains both hydrophilic monomers and lipophilic monomers, wherein the hydrophilic monomers provide carboxyl groups on the molecular chain. When potassium carbonate and sodium carbonate in solution B are added to the system, a large number of carboxyl groups are neutralized to form salts, electrostatic repulsion is generated in the molecules, the macromolecular chains gradually extend, and a large number of water molecules around are adsorbed, thereby limiting the free movement of the water molecules. In addition, after the calcium-based bentonite in component C is added, the calcium-based bentonite particles are also bound between the molecular chains and are difficult to move, so the viscosity of the system is increased in appearance. The butyl acrylate main chain based on the lipophilic monomer and the hydrophobic groups provided by the macromolecular functional monomers can be intermolecularly associated with the latex particles in the emulsion to form a large three-dimensional network structure, which in turn limits the free movement of the latex particles and the calcium-based bentonite in the system, thereby further increasing the viscosity of the system.

[0067] Guar gum and borax are used for crosslinking on the market, and the gelling speed is fast, but it is not sticky and has poor fluidity. In comparative example 1, material B does not use sodium carbonate and potassium carbonate, but uses sodium bicarbonate and sodium acetate instead. After material B and material A react, the solution is relatively thin and cannot adhere to the glass plate; comparative example 2 uses sodium sulfite instead, and the solution after the three components are mixed is even thinner and cannot reach the thickness of the embodiment.

[0068] As can be seen from Table 1, this material has no temperature rise and reacts quickly; it has good adhesion and can remain on the glass plate without sliding down; and it has excellent blocking performance and can maintain negative pressure for a long time after pumping negative pressure. When applied, the three-cylinder grouting pump independently developed by Xuzhou Ji'an Mining Technology Co., Ltd. is used to pump three components simultaneously, which is simple to operate, has excellent performance, and has broad application prospects.

[0069] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A plastic material for plugging underground in coal mines, consisting of three components: material A, material B and material C, characterized in that: The composition of material A by weight is: 30-50 parts of homemade gelling agent and 50-70 parts of water; The composition of material B by weight is: 6-9 parts of potassium carbonate, 3-6 parts of sodium carbonate, and 85-90 parts of water; The C material is composed of 10-15 parts by weight of white calcium-based bentonite.

2. The plastic material for plugging underground coal mines according to claim 1, characterized in that: The self-made gelling agent is made from the following raw materials in parts by weight: 52-60 parts of butyl acrylate, 30-40 parts of isooctyl acrylate, 5-10 parts of styrene, 2-4 parts of acrylamide, 0.2-0.5 parts of diallyl phthalate, 5-8 parts of behenyl polyoxyethylene ether methyl methacrylate, 3-5 parts of octadecyl acrylate, 2-8 parts of sorbitan monooleate, 0.1-0.5 parts of stearyl alcohol polyoxyethylene ether, 2.5-4 parts of MES-30, 0.1-0.2 parts of Na2HPO4, 50-100 parts of initiator, and 230-260 parts of water.

3. The plastic material for plugging underground coal mines according to claim 2, characterized in that: The preparation method of the self-made gelling agent comprises the following steps: S1: Weigh and add part of water, part of MES-30 and sorbitan monooleate according to the ratio into a pre-emulsification bottle, stir and mix, then weigh butyl acrylate, acrylamide, isooctyl acrylate, styrene, behenyl polyoxyethylene ether methyl methacrylate, octadecyl acrylate, diallyl phthalate according to the ratio and drop them into the pre-emulsification bottle in sequence, stir and mix, and prepare a stable pre-emulsion; S2: taking out 5-10% of the pre-emulsion as the seed emulsion, and continuing to stir the remaining pre-emulsion as the core layer pre-emulsion for standby use; S3: Add the remaining water to the reaction system, dissolve Na2HPO4, stearyl alcohol polyoxyethylene ether, and sorbitan monooleate in water according to the ratio, stir and heat to 80-85°C, and stir at a speed of 120-160r / min; S4: Add the seed emulsion and the first initiator in step S2 at 80-85°C, gradually drop the remaining core layer pre-emulsion and the second initiator, cool to 65-70°C after 2-4 hours and keep for 1-2 hours; then cool to 35-40°C, add the remaining emulsifier MES-30, stir evenly and discharge.

4. The plastic material for plugging underground coal mines according to claim 2, characterized in that: The initiator comprises a first initiator and a second initiator, the concentration of the first initiator is 5-10 wt %, and the concentration of the second initiator is 2-5 wt %.

5. The method for preparing a plastic material for underground coal mine plugging according to claim 4, characterized in that: The first initiator and the second initiator are both selected from any one of ammonium persulfate, potassium persulfate and azobisisobutyronitrile.

6. The plastic material for plugging underground coal mines according to claim 3, characterized in that: The mass fraction of the water added in step S1 is 100-120 parts.

7. The plastic material for plugging underground coal mines according to claim 3, characterized in that: The mass fraction of the MES-30 added in step S1 is 2-3 parts.

8. The plastic material for plugging underground coal mines according to claim 3, characterized in that: The mass fraction of the first initiator added in step S4 is 30-50 parts.

9. A method for preparing a plastic material for underground coal mine plugging according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Add the homemade gelling agent into water according to the proportion, stir evenly to obtain material A; S2: Add sodium carbonate and potassium carbonate into water according to the ratio, stir evenly to obtain material B; S3: Add water to material C to form solution C, with a mixing mass ratio of 1:2.5-4; S4: During the grouting process, material A, material B and solution C are mixed in a mass ratio of 2:2:1 and injected into the area to be plugged.